2015
DOI: 10.1002/xrs.2619
|View full text |Cite
|
Sign up to set email alerts
|

X-ray fluorescence determination of the manganese valence state and speciation in manganese ores

Abstract: a This work concerns determination of the manganese valence state and speciation by wavelength-dispersive X-ray fluorescence analysis. The authors investigated the effect of the manganese valence state and speciation on the intensity of some К-series lines of the X-ray emission spectrum for the samples of manganese compounds. The intensities of MnKβ 5 line and MnKβ′ satellite are least influenced by speciation, and they may be used for evaluating the manganese valence state for the samples containing low iron.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…The influence of the chemical bond results in the chemical shift of the SKα 1,2 peak (1–2 eV) and in intensity of satellite SKα 3,4 . To clearly recognize the differences in intensities, the approach earlier described and successfully employed for manganese and iron spectra has been applied. The relative spectra were constructed by normalizing obtained spectra per intensity maximum of reference sulfur‐rich sample (elemental sulfur) spectrum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the chemical bond results in the chemical shift of the SKα 1,2 peak (1–2 eV) and in intensity of satellite SKα 3,4 . To clearly recognize the differences in intensities, the approach earlier described and successfully employed for manganese and iron spectra has been applied. The relative spectra were constructed by normalizing obtained spectra per intensity maximum of reference sulfur‐rich sample (elemental sulfur) spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…The authors earlier proposed the techniques for determination of iron chemical state in rocks and manganese chemical state and speciation in ores with the Kβ 5 to Kβ 1,3 line intensities ratio. Sulfur speciation can be quantitatively estimated with the SKβ′ satellite to SKβ 1,3 line intensity ratio by the wavelength‐dispersive XRF analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Results for FeO in excess of 1.5% m m À1 in igneous rocks of basic and ultrabasic composition were reported to have errors below 10% relative (comparable to titrimetric analysis), although the authors admitted that results for alkaline rocks might be in excess of 50% relative. In a second contribution, Chubarov et al 132 proposed a similar technique for the determination of Mn valence states. They reported that the Mn Kb 5 and Mn Kb 0 were least affected by speciation, whereas the Mn Kb 00 and Mn Kb x were suitable for assessing Mn speciation.…”
Section: Geological and Climate Changementioning
confidence: 99%
“…Mn possesses the 3d 5 4s 2 electronic configuration, and the manganese ion with various valences presents very abundant photoelectric properties, which is paid significant attentions to the band gap and photoluminescence (PL) of manganous compounds (MCs). 6 As the development and improvement of characterization technology, further exploration of the physical properties of MCs in this work is motivated by their potential in optical applications. 7,8 Recent investigations in MnCl 2 indicated that it can be treated as an ideal catalyst and doping material.…”
Section: Introductionmentioning
confidence: 99%
“…The interesting phenomenon observed in the family of TMDs is the wide optical band gap and large resistivity, which makes them ideal optical materials for applications. The traditional manganese dichloride (MnCl 2 ) is important both in practical applications and in fundamental science, which has attracted significant research interest in decades. Mn possesses the 3 d 5 4 s 2 electronic configuration, and the manganese ion with various valences presents very abundant photoelectric properties, which is paid significant attentions to the band gap and photoluminescence (PL) of manganous compounds (MCs) . As the development and improvement of characterization technology, further exploration of the physical properties of MCs in this work is motivated by their potential in optical applications. , …”
Section: Introductionmentioning
confidence: 99%